Translating sustainable and smart city strategies into performance measurement systems. Issue 3 (16th April 2018) - Brorström, Sara; Argento, Daniela; Grossi, Giuseppe; Thomasson, Anna; Almqvist, Roland
Abstract : This paper shows how sustainable and smart strategies can be implemented in cities and how these strategies influence, and are influenced by, performance measurement systems. Drawing upon the Foucauldian notion of governmentality, the authors present the case of Gothenburg in Sweden, where they interviewed the key actors involved in a new sustainability strategy. Translating strategy into performance measurement systems requires collaboration across organizational boundaries and considerations of financial goals and social and human aspects.